STRUGGLE FOR SURVIVAL OF ANDY DUFRESNE IN FRANK DARABONT'S SHAWSHANK REDEMPTION MOVIE 1994: AN INDIVIDUAL PSYCHOLOGICAL APPROACH - Agustina, intan (2010)
The major problem of this study is how struggle for surviving is reflected in Shawshank Redemption movie based on individual psychological approach. This study analyses structural elements of Shawshank Redemption movie and Andy Dufresne's struggle for survival based on individual psychological point of view. This research paper is qualitative research. The object of the study is Andy Dufresne in Shawshank Redemption movie directed by Frank Darabont in 1994 by Warner Bross Pictures. The primary data is Shawshank Redemption movie itself and the secondary data are taken from the other data, which have relation with the research, the underlying theory and other materials concerned to the analysis, such as biography of the director, some books of psychology, website about the movie and homepage of the movie. The technique of data analysis is descriptive analysis. The result of the study shows the close relationship between Shawshank Redemption movie and an individual psychology, particularly in human striving for survival. Shawshank Redemption movie directed by Frank Darabont is about someone's struggle for his goals of life.